2017
DOI: 10.7860/jcdr/2017/21938.9169
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Gengigel ® Application in the Management of Furcation with Coronally Advanced Flap through Surgical Re-Entry- A Split Mouth Clinical Study

Abstract: Both Gengigel® with coronally positioned flap and coronally positioned flap alone are effective in the treatment of Grade II furcation defects. The combination of Gengigel® with coronally positioned flap leads to better results in hard tissue measurement as compared to coronally positioned flap alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
1
5
0
2
Order By: Relevance
“…Gengigel ® contains 0.2% hyaluronic acid (HA) gel that provides stability and elasticity to tissues and delays penetration of viruses and bacteria. 66 This experiment confirmed that a mixture of HA and sEV in an appropriate ratio can still maintain the injectability and release 80% of sEV slowly within one week without affecting the biological functions of sEV. Therefore, HA is a convenient, safe, and effective scaffold material that is suitable for auxiliary sEV in clinical applications.…”
Section: Discussionsupporting
confidence: 65%
“…Gengigel ® contains 0.2% hyaluronic acid (HA) gel that provides stability and elasticity to tissues and delays penetration of viruses and bacteria. 66 This experiment confirmed that a mixture of HA and sEV in an appropriate ratio can still maintain the injectability and release 80% of sEV slowly within one week without affecting the biological functions of sEV. Therefore, HA is a convenient, safe, and effective scaffold material that is suitable for auxiliary sEV in clinical applications.…”
Section: Discussionsupporting
confidence: 65%
“…Additionally, rubbing for 1–2 min to achieve the proper effect is difficult in practice. 10 Therefore, challenges remain to be addressed in the field of HA delivery.…”
Section: Introductionmentioning
confidence: 99%
“…This barrier function of hyaluronic acid is very important in the wound healing process, and it is a very promising material for improving the results of periodontitis treatment. [42][43][44][45][46][47] Results our study show that Gengigel Hyaluronic acid preparation used in combination with collapan is a good adjunct to conventional periodontitis therapy. Study demonstrates the higher efficiency and osteoconductive properties of CollapanL for the repair of intrabone defects.…”
Section: Citation: Hakobyan G (2022) Et Al Correlation Of Level Bone ...mentioning
confidence: 63%